2016
DOI: 10.1016/j.ecoleng.2015.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic culturable bacteria colonizing Lavandula dentata L. plants: Isolation, characterization and evaluation of their plant growth-promoting activities

Abstract: Aromatic plants such as lavender are stirring the attention of many researchers due to their content in bioactive secondary metabolites that can be used in traditional medicine. However, information regarding naturally occurring lavender associated bacterial endophytes (BE) is limited. To the best of our knowledge, this is the first study which aims to assess the phylogenetic diversity of the culturable endophytic bacteria of Lavandula dentata cultivated under organic management and to evaluate their potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 31 publications
2
27
0
2
Order By: Relevance
“…All strains that we isolated were IAA producers (Table 2 ). Similarly, other authors observed that a vast majority of endophytic bacteria synthesized IAA (Etesami et al 2014 ; Kukla et al 2014 ; Pawlik and Piotrowska-Seget 2015 ; Pereira et al 2016 ; Xu et al 2016 ). The application of these strains could contribute to improve root proliferation and elongation that is crucial during phytoremediation as well as in growth and development of economical important crops such as potatoes, maize, and rice (Garbeva et al 2001 ; Ikeda et al 2010 ; Seghers et al 2004 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…All strains that we isolated were IAA producers (Table 2 ). Similarly, other authors observed that a vast majority of endophytic bacteria synthesized IAA (Etesami et al 2014 ; Kukla et al 2014 ; Pawlik and Piotrowska-Seget 2015 ; Pereira et al 2016 ; Xu et al 2016 ). The application of these strains could contribute to improve root proliferation and elongation that is crucial during phytoremediation as well as in growth and development of economical important crops such as potatoes, maize, and rice (Garbeva et al 2001 ; Ikeda et al 2010 ; Seghers et al 2004 ).…”
Section: Discussionmentioning
confidence: 63%
“…The cellulase secretion and motility of endophytic bacteria may help in the process of plant colonization and spread of bacteria in the host plant. Verma et al ( 2001 ) and Pereira et al ( 2016 ) described the cell wall-degrading enzymes from endophytic bacteria, demonstrating their potential for plant tissues colonization. The ability of bacterial strains to colonize roots appears to be crucial for a close interaction between plants and bacteria especially in hazardous environments.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning fungi, the genus Acremonium is worth mentioning for its involvement in plant growth [40]. On the other hand, in the Frantoio endosphere, the bacterial genera Neorhizobium, Bradyrhizobium (able to form nitrogen fixing nodules in legumes and nodule-like structure in radish, tomato, and rice [41]), Sphingomonas (reported to increase Chinese medicinal plant [42] biomass), Actinoplanes (involved in cucumber [39] growth promotion), and Caulobacter (reported as phytohormones producer in lavender [43]) were significantly more abundant. With regard to fungi and as reported for the rhizosphere, the genera Trichoderma, a wellknown PGPM and BCA, and Acremonium were also found (e.g., [44]).…”
Section: Discussionmentioning
confidence: 99%
“…Plant-associated microbes live in plant tissue endophytically or symbiotically or they colonize the root surface and cooperate with each other by producing various metabolically active substances ( Egamberdieva, 2011 , 2012 ; Berg et al, 2013 ; Asaf et al, 2017 ). The stimulation of plant growth and nutrient acquisition by beneficial rhizobacteria has been correlated to the biosynthesis of plant growth regulators, including auxins ( Etesami et al, 2015 ; Pereira et al, 2016 ), gibberellins ( Khan et al, 2014 ), cytokinins ( Kudoyarova et al, 2014 ), and ABA ( Sgroy et al, 2009 ). The microbial regulators modulate plant hormone levels in plant tissue, and they have been found to have effects that are similar to exogenous phytohormone application ( Egamberdieva, 2009 ; Turan et al, 2014 ; Shahzad et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%